Informed consent and bioethical advances in clinical settings - Giacobello, Maria Laura (Frontiers in Psychology, 2025)
The increasing integration of artificial intelligence (AI) in healthcare, despite the still uncertain implications for clinical practice, underscores the vast array of opportunities it brings to medicine. The benefits of technological enhancement in this domain are clear and substantial. However, this same context gives rise to equally significant ethical concerns, particularly in relation to data security, confidentiality, equitable access, and the attribution of responsibility. AI’s emergence in clinical settings introduces complexities that traditional informed consent procedures are not fully equipped to address, prompting ethical, legal, and practical concerns around information delivery and patient autonomy. Effective physician-patient communication is critical to ensuring informed and voluntary adherence to treatment. Such communication also plays a pivotal role in supporting patients’ psychological well-being and encouraging their active involvement in care. AI’s role as a third party in the therapeutic relationship necessitates a serious examination of the new risks it introduces. Bioethics must provide a prudent and critical framework to evaluate and ethically guide the development and deployment of such technologies. This constitutes both a technical and moral challenge. In Ethics of Artificial Intelligence, Floridi observes that major ethical frameworks for AI converge with the principles first formulated by Beauchamp and Childress in Principles of Biomedical Ethics (1979): autonomy, non-maleficence, beneficence, and justice. Floridi argues for the inclusion of a fifth principle, explicability, as essential in addressing the opacity of AI systems. Explicability, requiring that AI processes be comprehensible and transparent, is intrinsically linked to the principle of autonomy and its practical expression: informed consent. The integration of AI into clinical practice directly affects the moment when a physician’s duty to inform meets the patient’s right to autonomy. The traditional principlist model identifies challenges in the communication of information: an area now further complicated by AI’s opacity. This raises pressing questions about the physician’s obligation to disclose AI involvement in care decisions. Ultimately, as the therapeutic relationship evolves from a dyadic to a triadic model, physician, patient, and AI, there is a need to reassess informed consent practices, with sustained commitment to the core ethical values of transparency and autonomy.